Empowering Indonesian Adolescents Through Digital Health Literacy: A Predictive Model for Breast Cancer Prevention Education Aligned with SDG 3 - Irma, Irma; M.Sallo, Andi Kamal; Marlina, Marlina; Subair, Nurlina (Journal of Scientific Insights, 2025)
Indonesia faces unique challenges with breast cancer affecting younger populations, necessitating early health literacy interventions among adolescents to achieve SDG 3.4 targets. To develop a predictive model identifying determinants of breast cancer literacy among Indonesian adolescents. A cross-sectional study was conducted from March-June 2025 in West Sulawesi Province. The sample comprised 58 female adolescents (ages 14-17) from high schools (n=26, 44.8%) and vocational schools (n=32, 55.2%). Data collection utilized validated online surveys measuring ten breast cancer literacy indicators. Binary logistic regression with backward elimination was performed using SPSS 25.0. Overall, 56.9% (n=33) demonstrated inadequate literacy levels, with only 43.1% (n=25) achieving adequate levels. Critical knowledge deficits were found in prevention strategies (1.7% correct) and risk factor identification (37.3% correct), contrasting with high awareness of medical follow-up procedures (96.6% correct). The logistic regression model (Nagelkerke R²=0.618, Hosmer-Lemeshow p=0.512) identified four significant determinants: enrollment in high schools versus vocational schools (OR=4.3, 95% CI: 1.27-14.55, p=0.019), healthcare provider information sources (OR=7.3, 95% CI: 1.44-10.46, p=0.016), digital learning media utilization (OR=3.4, 95% CI: 1.13-10.46, p=0.031), and frequent health information-seeking behavior (OR=3.4, 95% CI: 1.01-11.66, p=0.048). This model enables targeted resource allocation for cancer prevention strategies supporting SDG 3.4, potentially reducing premature mortality through enhanced early detection behaviors among Indonesia's future generations.